Ultrafast response of photoexcited carriers in VO2 at high-pressure. (2nd August 2018) - Braun, Johannes M; Schneider, Harald; Helm, Manfred; Mirek, Rafał; Boatner, Lynn A; Marvel, Robert E; Haglund, Richard F; Pashkin, Alexej
Abstract: We utilize near-infrared pump—mid-infrared probe spectroscopy to investigate the ultrafast electronic response of pressurized VO2 . A clear anomaly in the linear mid-infrared response as well as in the fluence dependence of the pump–probe signal is observed around 8 GPa indicating a pressure-induced phase transition. Distinct pump–probe signals and a pumping threshold behavior typical for the insulating VO2 phase persist also in the high-pressure phase. Thus, in contrast to the temperature-induced rutile metallic state of VO2, the pressure-induced monoclinic phase preserves the energy gap. However, our results indicate the appearance and a gradual growth of additional intragap states upon increasing pressure above 8 GPa. These observations can be interpreted in terms of a bandwidth-controlled Mott–Hubbard transition.